The Analysis of The Green Banking Implementation Model on Banking Performance at Bank Syariah Indonesia: Analisis Model Implementasi Green banking Terhadap Kinerja Perbankan Pada Bank Syariah Indonesia KCP Banjarnegara - Enjen, Enjen Zaenal Mutaqin (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2023)
This study aims to examine the implementation of green banking practices at Bank Syariah Indonesia, KCP Banjarnegara, and their impact on banking performance. This study uses a descriptive qualitative approach with a field research method through direct observation and interviews with the Branch Manager, Operational Staff, teller, and microstaff of Bank Syariah Indonesia, KCP Banjarnegara. Indicators of green banking activities used in this study include green Product, green Operation, green customer, and green Policy. The results of this study indicate that Bank Syariah Indonesia KCP Banjarnegara implements green banking practices based on research indicators, such as Green Product, Green Operation, Green customer, and green policy. Bank Syariah Indonesia, KCP Banjarnegara, has implemented all indicators well. This has a positive impact on the image and reputation of Bank Syariah Indonesia, KCP Banjarnegara, as a bank that cares about the environment and social responsibility. In addition, the existence of Operational Efficiency in banking has helped Bank Syariah Indonesia KCP Banjarnegara increase efficiency and reduce costs. The use of technology also speeds up the transaction process and services for customers and increases customer satisfactio.